1716 Why do emergency department clinicians miss acute aortic syndrome? A case series and descriptive analysis. Issue 12 (22nd November 2022) - McLatchie, Rachel; Wilson, Sarah; Reed, Matthew; Ticehurst, Francoise; Easterford, Kathryn; Alawiye, Salma; Cowan, Alicia; Gupta, Aakash
Abstract : Aims, Objectives and Background: Acute aortic syndrome (AAS) is a rare, life-threatening emergency affecting approximately 4000 people per year in the UK, has an ED misdiagnosis rate as high as 38% and around one quarter of cases are not diagnosed until 24 hours after presenting to the ED. It presents in many atypical ways, posing a significant diagnostic conundrum for the emergency department (ED) clinician and risk of litigation. We sought to understand the reasons why AAS was missed in ED by conducting a case series review of patients with misidentified AAS presenting to three UK EDs over a 10-year period. Method and Design: We identified missed diagnoses of AAS using searches of ED morbidity and mortality records, post-mortem reports, complaints, Electronic Patient Records (EPRs) and Radiology records from three UK EDs. Results and Conclusion: Between 1.1.2011–31.12.2020, 43 cases were identified across three EDs (1.4 cases/yr/dept). The most common diagnosis was Type A aortic dissection (22; 51%). The most common incorrect presumed diagnoses made were acute coronary syndrome (ACS, 12; 28%), pulmonary embolism (PE, 5; 12%) and 'non-specific chest pain' (5; 12%). In 31 of the 43 cases (72%) there was no evidence from the notes of consideration of AAS in the differential diagnosis. In 10 of the 43 cases (23%), AAS was clearly considered, but the clinician appears to have been falsely reassured by clinical findings, normal chest x-ray, or atypical or resolved symptoms. Only 63% (27/43) presented with chest pain and 16% (7/43) had no pain. 65% (28/43) documented sudden onset of symptoms. This case series reinforces the RCEM/RCR recommendation that 'All clinicians working in the emergency department should be made aware of the difficulties in excluding the diagnosis of thoracic aortic dissection.' Further research is required to improve ED diagnostic pathways for this group of patients.